Characteristics of self-medication assessment instruments in Brazil: an integrative review - Barreto, Márcio Adriano Fernandes; Negreiros, Francisca Diana da Silva; Cestari, Virna Ribeiro Feitosa; Maia, Clécio André Alves da Silva; Sampaio, Helena Alves de Carvalho; Moreira, Thereza Maria Magalhães (Revista de Enfermagem da UFPI, 2024)
Objective: To describe the characteristics of self-medication assessment instruments with evidence of validity in Brazil. Methods: An integrative review, without temporal delimitation, with collection in the LILACS, Scopus, PubMed, MEDLINE and Web of Science databases. Ten studies related to five instruments were included. Results: The most convergent domains were sociodemographic aspects, self-medication practice, reasons, medications used and recommendation/sources. Self-medication was assessed by only one instrument with evidence of validity, but it was multidimensional, making its application difficult. The instruments showed good reliability indices, however, of the five, one did not measure reliability. The good psychometric properties of the self-medication and temporomandibular pain instrument stand out (Kappa: 0.810, Cronbach’s alpha: 0.844). Conclusion: The different instruments analyzed present limitations in evidence of validity, showing the need to develop an instrument focused on self-medication that is reliable and valid.